Growth and nutrition: preliminary findings from the 2016 Young Lives Survey (Round 5): Ethiopia - Woldehanna, T; Araya, M; Pankhurst, A (Young Lives, 2018)
This fact sheet presents findings from the fifth round of the Young Lives survey of children in Ethiopia.The data show that indicators of nutrition have improved with decreased levels of stunting, thinness, and household food insecurity, which are probably related to better access to sanitation and drinking water. However, overall rates of stunting and thinness still remain high, and some households moved from being food secure to mildly food insecure, probably as a result of the recent El Niño-driven drought, so that nutrition interventions continue to be important.